An accurate and universal protein-small molecule batch docking solution using Autodock Vina - Che, Xinhao; Liu, Qilei; Zhang, Lei (Results in engineering, 2023)
As an important theoretical computation method in computer-aided drug design, molecular docking has significantly shifted the paradigm of drug discovery. As one of the open-source docking software, Autodock Vina (Vina) is widely popular, but the lack of relevant experience and inappropriate docking parameters make it unable to perform optimally in practical application scenarios, which leads to potential failure risks in the early stage of drug discovery. In order to simplify the docking steps and determine the most appropriate docking parameters, a universal solution for rigid receptor docking using Vina has been proposed in this paper, and a user-friendly software for the entire process of molecular docking using Vina is developed. The case studies show that our docking solution is able to be applied to different docking scenarios to facilitate a more accurate, faster, and more convenient new drug discovery process. •An accurate and universal batch docking solution using Autodock Vina is proposed.•The optimal parameters for batch docking with Vina are determined.•A user-friendly software interface is developed for docking with Vina.